PECULIARITIES OF SELF-ESTEEM AND SELF-ATTITUDE IN ADOLESCENCE - M A Rushina; A V Orlova (Peoples' Friendship University of Russia (RUDN University), 2015)
The paper presents the results of the research devoted to the study of gender characteristics of self- esteem and self-attitude in adolescence. Namely, the work considers the theoretical framework of the study and some empirical results of self-assessment and self- attitude. Adolescence was not chosen by chance. It is at this time that there happens a qualitative transformation of consciousness, when the former, children's and adolescents' self-image changes and becomes more mature, objective. The analysis of the literature showed that the problem of identifying the level of self-esteem and self-attitude still remains topical and one of the most studied, especially because the work was focused on gender differences. When there were questions about the study of self-comprehension of the person, the task of reconstruction of the ontogenesis of the conscious self was solved through observing the children and through the analysis of graphic images and texts. Since the 1930s the interest in the study of consciousness has increased dramatically and still has not subsided. As a rule, the subject of such studies are the structure and components of self-consciousness, i.e. how the individual perceives and describes him/herself, what properties of the body and the personality he/she realizes more clearly; mental processes and operations with the help of which the individual realizes, evaluates and defines him/ herself and his/her behavior; the psychological functions of self-consciousness, i.e. how adequate the self-image and personal self-assessment are, what role they play in the self-regulation of behavior.